Level-Set-based Wheel–Rail Profile Evolution in Four-Dimensional Continuous Functional Space. (March 2023) - Liu, Long; Yi, Bing; Shi, Xiaofei
Abstract: Wear of wheel treads and rails during service is a fundamental problem in railway lifecycle management. The change in the geometric shape of their profiles significantly affects the comfort and safety of the running train. Current studies primarily focus on the discrete geometry modeling of service wheel and rail profiles owing to the lack of dynamic and continuous modeling methods. Therefore, a physical data-driven method for wheel–rail profile evolution is proposed by constructing velocity fields with a level-set operator in a four-dimensional continuous functional space. A map is also proposed that connects both the measured and predicted profile data on the one hand, to the level-set operator, on the other hand, that efficiently and effectively evolves the wheel–rail profile during service. Illustrative examples demonstrate the effectiveness of the proposed method for wheel–rail profile evolution during lifecycle services. Generality and good precision for various profiles and wear scenarios can be used to continuously analyze the mechanics of wheel–rail contact, as well as profile optimization using gradient-based methods incorporating lifecycle properties. To the best of our knowledge, this is the first attempt to dynamically and continuously model wheel–rail profiles during lifecycle services using the measured and predicted profile data. Highlights: A novel method for dynamic geometry modeling of life-cycle service is proposed. The measured data driven method for evolving the wheel–rail profile is introduced. The pipeline of the physical driven wheel–rail profile evolution is also detailed. The wheel–rail profile evolution in continuous functional space is demonstrated. New application of level sets to dynamical and continuous geometry modeling.